GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 2855 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "TaxonKey is Aedes japonicus japonicus", "HasGeospatialIssue is false" ] }. The dataset includes 2855 records from 4 constituent datasets: 1 records from Ibaraki Nature Museum, Arthropoda collection. 61 records from Surveillance exotic mosquitoes in Belgium. 13 records from Geographically tagged INSDC sequences. 2780 records from VectorBase (Bioinformatics Resource for Invertebrate Vectors of Human Pathogens). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences